2020
DOI: 10.1002/jbmr.4623
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Late Pregnancy Dietary Inflammatory Index (DII) and Offspring Bone Mass: A Meta-Analysis of the Southampton Women's Survey (SWS) and the Avon Longitudinal Study of Parents and Children (ALSPAC)

Abstract: Systemic inflammation is associated with reduced bone mineral density and may be influenced by pro-inflammatory diets. We undertook an observational analysis of associations between late pregnancy energy-adjusted dietary inflammatory index (E-DII) scores and offspring bone outcomes in childhood. E-DII scores (higher scores indicating pro-inflammatory diets) were derived from food frequency questionnaires in late pregnancy in two prospective mother-offspring cohorts: the Southampton Women's Survey (SWS) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…A dietary challenge may have provided an environment where the RR may have resulted in programming of bone development. A recent study of two maternal-offspring cohorts (Southampton Women’s Survey and Avon Longitudinal Study of Parents and Children) has shown a correlation between a higher late pregnancy dietary inflammatory index and offspring bone health at 9 years of age, specifically a lower bone mineral content and BMD [ 2 ]. In line with this study are previous findings that RR could benefit the bone through modulation of potential antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dietary challenge may have provided an environment where the RR may have resulted in programming of bone development. A recent study of two maternal-offspring cohorts (Southampton Women’s Survey and Avon Longitudinal Study of Parents and Children) has shown a correlation between a higher late pregnancy dietary inflammatory index and offspring bone health at 9 years of age, specifically a lower bone mineral content and BMD [ 2 ]. In line with this study are previous findings that RR could benefit the bone through modulation of potential antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that maternal diet can set a trajectory for bone health of offspring [ 1 , 2 ]. Findings from these human studies align with preclinical studies reporting effects of diet including the level and type of fat, low protein content, general undernutrition or overnutrition, as well as polyphenols, to program offspring bone health [ [3] , [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%
“…No specific link to further development of menopausal osteoporosis in females suffering with PAO/LAO has yet been established; some data have suggested that girls born from mothers with PAO have lower BMD than controls, probably in common with the genetic background of their mothers [23,24]. The MAVIDOS (Maternal Vitamin D Osteoporosis Study) trial showed a higher BMD of offspring by the age of 4 to whom consistent maternal vitamin D (VD) supplementation was provided, VD deficiency being identified in a subgroup of females confirmed with PAO/LAO [25].…”
Section: The Frame Of Pao/laomentioning
confidence: 99%
“…Similarly, in over 50,000 mother–offspring pairs in the Danish National Birth Cohort study, a more Western diet in mid-pregnancy, characterised by high intakes of meat, potatoes and white bread but low fruit and vegetable intake, was associated with higher offspring risk of childhood forearm fracture [ 55 ]. More recently published work using the SWS and ALSPAC birth cohorts showed maternal consumption of a diet with a high dietary inflammatory index was negatively associated with offspring BA, BMC and aBMD in childhood [ 56 ].…”
Section: Maternal Nutrition In Pregnancy and Offspring Bone Healthmentioning
confidence: 99%